Effects of developmental manganese, stress, and the combination of both on monoamines, growth, and corticosterone - Charles V. Vorhees; Devon L. Graham; Robyn M. Amos-Kroohs; Amanda A. Braun; Curtis E. Grace; Tori L. Schaefer; Matthew R. Skelton; Keith M. Erikson; Michael Aschner; Michael T. Williams (Toxicology Reports, 2014)
Developmental exposure to manganese (Mn) or stress can each be detrimental to brain development. Here, Sprague-Dawley rats were exposed to two housing conditions and Mn from postnatal day (P)4–28. Within each litter two males and two females were assigned to the following groups: 0 (vehicle), 50, or 100 mg/kg Mn by gavage every other day. Half the litters were reared in cages with standard bedding and half with no bedding. One pair/group in each litter had an acute shallow water stressor before tissue collection (i.e., standing in shallow water). Separate litters were assessed at P11, 19, or 29. Mn-treated rats raised in standard cages showed no change in baseline corticosterone but following acute stress increased more than controls on P19; no Mn effects were seen on P11 or P29. Mn increased neostriatal dopamine in females at P19 and norepinephrine at P11 and P29. Mn increased hippocampal dopamine at P11 and P29 and 5-HT at P29 regardless of housing or sex. Mn had no effect on hypothalamic dopamine, but increased norepinephrine in males at P29 and 5-HT in males at all ages irrespective of rearing condition. Barren reared rats showed no or opposite effects of Mn, i.e., barren rearing + Mn attenuated corticosterone increases to acute stress. Barren rearing also altered the Mn-induced changes in dopamine and norepinephrine in the neostriatum, but not in the hippocampus. Barren rearing caused a Mn-associated increase in hypothalamic dopamine at P19 and P29 not seen in standard reared Mn-treated groups. Developmental Mn alters monoamines and corticosterone as a function of age, stress (acute and chronic), and sex.